2020
DOI: 10.3389/fphys.2020.00813
|View full text |Cite
|
Sign up to set email alerts
|

The Energy of Muscle Contraction. I. Tissue Force and Deformation During Fixed-End Contractions

Abstract: During contraction the energy of muscle tissue increases due to energy from the hydrolysis of ATP. This energy is distributed across the tissue as strain-energy potentials in the contractile elements, strain-energy potential from the 3D deformation of the base-material tissue (containing cellular and extracellular matrix effects), energy related to changes in the muscle's nearly incompressible volume and external work done at the muscle surface. Thus, energy is redistributed through the muscle's tissue as it c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(91 citation statements)
references
References 90 publications
(152 reference statements)
6
85
0
Order By: Relevance
“…Strain-energy is the energy stored by a system undergoing deformation. We previously showed that the redistribution of strain-energy potentials within contracting muscle (Wakeling et al, 2020) changes with the pennation angle, and it is likely that work done on and by the muscle generated by forces in the transverse direction would also affect the strain-energy potentials within the muscle (Wakeling et al, 2020). Thus, we would expect that the external transverse loads affect the strain-energy potentials within the muscle, that in turn could explain the changes in force in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Strain-energy is the energy stored by a system undergoing deformation. We previously showed that the redistribution of strain-energy potentials within contracting muscle (Wakeling et al, 2020) changes with the pennation angle, and it is likely that work done on and by the muscle generated by forces in the transverse direction would also affect the strain-energy potentials within the muscle (Wakeling et al, 2020). Thus, we would expect that the external transverse loads affect the strain-energy potentials within the muscle, that in turn could explain the changes in force in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 95%
“…Not all muscles increase in thickness during fixed-end contractions, and thus we should not expect that every muscle will squeeze into neighbouring muscles when they activate. Muscles with lower pennation angles (<15 • ) tend to bulge, whereas more pennate muscle may thin as they activate Wakeling et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations